Performance Analysis of Multi-Body Modeled Washing Machines (MBomWM) - Asiya E. Asiya; Yomobong Amos I; Effiong A. Archibong (International Journal of Engineering and Management Research, 2020)
One of the key features of an automated washing machine is the noise and vibration it produces, or more technically, the decibel level it produces. Numerous of home appliance companies have put in much effort to solve this problem but there is still large room for further improvements especially in the rinse and the spin cycles of a washing machine. This work illustrates the performances of multi-body modelled of washing machines realized with the aim to analyze the vibrational acoustic emission. An experimental measurement has been carried out using a digital sound level meter (SLM) to determine the overall noise produced by four different modelled of automated washing machines with a view of noting the model with the highest sound pressure level during the three different cycles (the wash, rinse and spin). Results show that all the machines produced their highest noise during the spinning cycle. Out of the four different models considered, IPSO HF: 304 has the highest sound level of 99.62 during its spin cycle when a maximum load of 30Kg was applied, followed by Imesa RC 23 with a 96.13. On the other hands, LG: Direct Drive 13 has the least sound pressure level of 84.75. With this knowledge in mind, one can advise a buyer of which model to purchase from the market and if an operator must use the machine, how long he can operate such machine without health challenges.